PEMBERDAYAAN PEMUDA DESA KACE TIMUR MELALUI PELATIHAN APLIKASI PERKANTORAN - Yanuarti, Elly; Melati Suci Mayasari; Rahmat Sulaiman; Tri Sugihartono; Mardeka Raya, Agustina; Brotosaputro, Goenawan (ISB Atma Luhur, 2025)
Computer skills have become one of the basic requirements for young people in facing the challenges of the digital age. Young people in Kace Timur Village still have limitations in operating computer devices, especially in word processing and presentation preparation. This community service activity aims to provide computer training to 56 young people in Kace Timur Village, which was held at the Kace Timur Village Office. The implementation method uses a hands-on training approach guided by the implementation team. The results of the activity show an increase in participants' understanding of the basics of document processing with Microsoft Word and the ability to create presentations with Microsoft PowerPoint. This training is expected to improve the competence of the village youth in supporting educational, organizational, and digital-based entrepreneurial activities.